Bulbophyllum salweenensis (Orchidaceae; Epidendroideae; Malaxideae), a new species from Yunnan, China - Zhou, Tingting; Jin, Xiaohua (Phytotaxa, 2015)
Bulbophyllum Thouars (1822: tab. 3) is among the largest genera of Orchidaceae, comprising about 2200 species widely distributed in tropical Africa, Asia and America (Pridgeon et al. 2014). There are several centres of species diversity, including Madagscar (200 species), New Guinea (600 species), and continental Asia (400 species). There are about 120 species in China, out of which 45 species (Tsi 1999, Li 2003, Chen & Vermeulen 2009). During fieldwork in northern Yunnan, a new species of Bulbophyllum described below was found.